Galvanic Corrosion between Carbon Steel and Soldering Fluxes in a Concentrated LiBr Solution at High Temperatures - KIKUCHI, Tomoko; MABUCHI, Katsumi; TAKAHASHI, Hideaki (Hyōmen gijutsu, 1998)
Galvanic corrosion between carbon steel and soldering fluxes was studied in a concentrated LiBr solution at 383 and 433K, using extreme-value statistical analysis of pit depth in soldered parts, measurement of the amount of dissolved Fe2+ and dissolved flux compornents, and corrosion potential and galvanic current measurement. The soldering fluxes used were copper, copper alloys (Cu-Si-Mn, BAg-8, Ag 30-Cu, 70/30 Cupronickle) and nickel. Nickel flux soldered with carbon steel caused considerable galvanic corrosion of carbon steel at 383K, while carbon steel soldered with copper and copper alloy fluxes showed galvanic corrosion of the fluxes at 383 and 433K. The galvanic corrosion rate of fluxes decreased in the order of copper>Cu-Si-Mn>Ag 30-Cu>BAg-8> 70/30 cupronickel at 433K, and Cu-Si-Mn>copper>Ag 30-Cu>BAg-8>70/30 cupronickel at 388K. 70/30 cupronickel flux was considered the most suitable soldering flux in a concentrated LiBr solution at high temperature.